Migration patterns & their associations with health and human rights in eastern Myanmar after political transition: results of a population-based survey using multistaged household cluster sampling - Parveen K. Parmar; Charlene Barina; Sharon Low; Kyaw Thura Tun; Conrad Otterness; Pue P. Mhote; Saw Nay Htoo; Saw Win Kyaw; Nai Aye Lwin; Cynthia Maung; Naw Merry Moo; Eh. Kalu Shwee Oo; et al. (Conflict and Health, 2019)
Abstract Background Myanmar transitioned to a nominally civilian government in March 2011. It is unclear how, if at all, this political change has impacted migration at the household level. Methods We present household-level in- and out-migration data gathered during the Eastern Burma Retrospective Mortality Survey (EBRMS) conducted in 2013. Household level in-and out-migration information within the previous year was gathered via a cross-sectional, retrospective, multi-stage population-based cluster randomized survey conducted in eastern Myanmar. Univariate, bivariate and regression analyses were conducted. Results We conducted a cross-sectional survey of 6620 households across Eastern Myanmar between July and September of 2013. Out-migration outstripped in-migration more than 6:1 overall during the year prior to the survey – for international migration this ratio was 29:1. Most in-migrants had moved to their present location in the study area from other areas in Myanmar (87%). Only 11.3% (27 individuals) had returned from another country (Thailand). Those who migrated out of eastern Myanmar during the previous year were more likely to be male (55.2%), and three times more likely to be between the ages of 15–25 (49.5%) than non-migrants. The primary reason cited for a return to the household was family (26.3%) followed by work (23.2%). The primary reason cited for migrating out of the household was for education (46.4%) followed by work (40.2%). Respondents from households that reported out-migration in the past year were more likely to screen positive for depressive symptoms than households with no migration (PR 1.85; 95% CI 1.16, 2.97). Women in households with in-migration were more likely to be malnourished and had a higher unmet need for contraception. Forced labor, one subset of human rights violations experienced by this population, was reported by more in-migrant (8%) than out-migrant households (2.2%), though this finding did not reach statistical significance. Conclusions These analyses suggest that opportunities for employment and education are the primary drivers of migration out of the household, despite an overall improvement in stability and decrease in prevalence of human rights violations found by EBRMS 2013. Additionally, migration into and out of households in eastern Myanmar is associated with changes in health outcomes.